ChemInform Abstract: Catalytic Transformations of Alkynes via Ruthenium Vinylidene and Allenylidene Intermediates. Issue 29 (June 2016) - Varela, Jesus A.; Gonzalez‐Rodriguez, Carlos; Saa, Carlos
Abstract: Review: applications of various ruthenium vinylidenes